2018
DOI: 10.21475/ajcs.18.12.06.pne1049
|View full text |Cite
|
Sign up to set email alerts
|

Germination of guar (Cyamopsis tetragonoloba (L.) Taub.) genotypes with reduced temperature requirements

Abstract: Guar (Cyamopsis tetragonoloba (L.) Taub.) is an annual legume with a long crop cycle and high temperature threshold for seed germination (20-21°C). In semi-arid Mediterranean areas, inadequate soil warmth delays guar planting to May/early June and harvest to October-November, when high rainfall hinders seed maturation and lowers gum quality. Nine world guar genotypes (from India, Pakistan, USA, South Africa) were tested for germination capability and speed in response to temperature. All source seeds were fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Knowledge on seed germination requirements is crucial to assess the real potential of wild genetic resources to be exploited within agricultural systems [ 46 , 47 ]. This is particularly important for legumes, where the role of seed coat in imposing PY has been widely recognized [ 6 , 7 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on seed germination requirements is crucial to assess the real potential of wild genetic resources to be exploited within agricultural systems [ 46 , 47 ]. This is particularly important for legumes, where the role of seed coat in imposing PY has been widely recognized [ 6 , 7 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Climate. Temperature is one of the main environmental factors that affect seed germination [30]. It has to be considered at planting time keeping in mind the crop cycle which can be longer than 160 days in large cycle genotypes [30].…”
Section: Soil and Climatementioning
confidence: 99%
“…Temperature is one of the main environmental factors that affect seed germination [30]. It has to be considered at planting time keeping in mind the crop cycle which can be longer than 160 days in large cycle genotypes [30]. The climates considered as optimal for Mexico were both: the sub-humid zones cataloged as Aw, Bs, Cf and the temperate regions Cs and Cw (Table 1) while the optimum temperature was in the range of 25˚C to 30˚C.…”
Section: Soil and Climatementioning
confidence: 99%
“…Although the ecological optimum of guar perfectly matches to the conditions of the semi-arid climatic zone of the northwest of India (~27° N), several attempts have been made to introduce this crop into higher latitudes: in the southern states of the USA -Texas (~29° N), Arizona (~34° N), Oklahoma (~35° N) (Lubbers, 1987), in southern Italy (~39° N) (Gresta et al, 2018). The main complication for successful guar cultivation in the countries of the higher latitudes is the prolonged vegetation period of plants causing harvesting delay before the onset of autumn rains, which negatively affects the yield.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the guar plants completed their vegetation from mid-October to early November. Therefore, it was concluded that early maturity is a key breeding trait for this crop when cultivated in the Mediterranean region (Gresta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%